1984
DOI: 10.1073/pnas.81.23.7588
|View full text |Cite
|
Sign up to set email alerts
|

Infection of human endothelial cells by human T-lymphotropic virus type I.

Abstract: We studied the effects of human T-lymphotropic virus type I (HTLV-I) on human endothelial cells in vitro. During cocultivation with an HTLV-I producer cell line (C91/PL), endothelial cells formed characteristic multinucleated syncytial giant cells. Inoculation with concentrated cellfree supernatant fluid from C91/PL cultures produced similar cytopathic effects, which were neutralized by pretreatment with HTLV-I specific human serum. HTLV-I antigens were detected in the cytoplasm of the multinucleated cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 30 publications
1
53
0
1
Order By: Relevance
“…Productive transmission of natural HTLV-1 isolates to primary human endothelial cell cultures (Ho et al, 1984;Hoxie et al, 1984), monocyte and microglial cells (Hoffman et al, 1992), as well as basal mammary epithelial cells (LeVasseur et al, 1998) has been reported.…”
Section: Htlv-1 Tropism: In Vitro or In Vivo Veritas?mentioning
confidence: 99%
“…Productive transmission of natural HTLV-1 isolates to primary human endothelial cell cultures (Ho et al, 1984;Hoxie et al, 1984), monocyte and microglial cells (Hoffman et al, 1992), as well as basal mammary epithelial cells (LeVasseur et al, 1998) has been reported.…”
Section: Htlv-1 Tropism: In Vitro or In Vivo Veritas?mentioning
confidence: 99%
“…First, cell-free infection by HTLV is very inefficient and efficient infection of cells requires cocultivation of peripheral blood mononuclear cells (PBMC) with irradiated HTLV-producer cells. Secondly, although HTLV has the capacity to infect a number of cell types including T cells, B cells, endothelial cells, glial cells, and monocytes of both human and nonhuman origin (Ho et al, 1984;Hoffman et al, 1984;Akagi et al, 1992;Koyanagi et al, 1993), the only cells susceptible to HTLV transformation are primary T lymphocytes. For the context of this article transformation is defined as continuous growth in the absence of exogenous IL-2; immortalization is defined as continuous IL-2-dependent growth.…”
Section: Htlv Experimental Systemmentioning
confidence: 99%
“…Evidence suggests that HTLV-1 and HTLV-2 have the same primary receptor, which is expressed ubiquitously on the surface of numerous cell types (11,45,68,69). In contrast to their restricted in vivo and in vitro transformation tropism, in vitro infection with both HTLV-1 and HTLV-2 can be established in many vertebrate cell lines, including T cells, B cells, endothelial cells, glial cells, and monocytes (1,(29)(30)(31). Therefore, it would seem unlikely that the HTLV Env would be responsible for the distinct cellular transformation tropism between HTLV-1 and HTLV-2.…”
Section: Discussionmentioning
confidence: 99%